IMPLEMENTASI PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS IV SDN 56/1 DESA ARO : Penelitian Tindakan Kelas - Sonya Arvita Sari; Destrinelli; Indra Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low critical thinking skills of students in science learning in grade IV of SDN 56/1 Aro Village. The purpose of this study is to describe the application of the Problem Based Learning (PBL) model and the improvement of students' critical thinking skills after the application of the model. This research is a Classroom Action Research (CAR) which is carried out in two cycles, each including the planning, implementation, observation, and reflection stages. The research subjects were 22 students. Data were collected through observation and documentation. The results of the study showed an increase in students' critical thinking skills, indicated by the percentage of achievement of critical thinking indicators which increased from 40.91% in cycle I meeting I to 50% in meeting II, then increased to 81.82% in cycle II meeting I and 95.45% in meeting II. Thus, the Problem Based Learning model is effective in improving students' critical thinking skills in science learning.